Optimization of Nb2O5/g-C3N4/PPy as an electrode material for prevailing electrochemical performance - Manisha; Qaeemy, M. Taqi; Dhanda, Monika; Lata, Suman; Kumar, Harish; Sharma, Anshu (Frontiers in Energy Research, 2025)
The use of a ternary composite employing carbon material, polymer and metal oxide can effectively increase the performance of an electrode material used in Supercapacitors. Herein, we have facilely synthesized ternary composites of Nb2O5/g-C3N4/PPy (NGP) via in-situ polymerization reaction by systematically varying the amount of niobium pentoxide. The structural and morphological analysis of samples were examined through XRD, TGA, FESEM and BET, confirming a specific surface area of 68.936 m2/g for NGP composite. Nb2O5 nanoparticles prevent the restacking of g-C3N4 sheets and PPy form a spongy globular morphology around this structure resulting in enhanced electrochemical performance. Electrochemical assessments of the optimized composite, including CV, GCD, and EIS, revealed a specific capacitance of 1,290.15 F/g at 2 mV/s in 1 M H2SO4, with an energy density of 75.25 W h/kg at a power density of 450.01 W/kg, demonstrating the efficacy of the ternary composite strategy in advancing supercapacitor electrode properties. After 5000 CV cycles and 1000 GCD cycles, the electrode retained a specific capacitance of 95% and 91% of its initial value, respectively.